Bonding through context language and interactional alignment in Japanese situated discourse - Ide, Risako, 1966-; Hata, Kaori (Pragmatics & beyond ;, 2020)
"This book examines the linguistic and interactional mechanisms through which people bond or feel bonded with one another by analyzing situated discourse in Japanese contexts. The term "bonding" points to the sense of co-presence, belonging, and alignment with others as well as with the space of interaction. We analyze bonding as established, not only through the usage of language as a foregrounded code, but also through multi-layered contexts shared on the interactional, corporeal, and socio-cultural levels. The volume comprises twelve chapters examining the processes of bonding (and un-bonding) using situated discourse taken from rich ethnographic data including police suspect interrogations, Skype-mediated family conversations, theatrical rehearsals, storytelling, business email correspondence and advertisements. While the book focuses on processes of bonding in Japanese discourse, the concept of bonding can be applied universally in analyzing the co-creation of semiotic, pragmatic, and communal space in situated discourse"--